IMPLEMENTASI KNOWLEDGE MANAGEMENT DAN PENGARUHNYA TERHADAP KINERJA KARYAWAN (Studi Pada Kantor BPJS Ketenagakerjaan Jawa Tengah dan DIY) - Irawan, Andrian Candra; Djastuti, Indi (Faculty of Economics and Business Diponegoro University, 2016)
This study aimed to analyze the influence of personal knowledge, job procedures and technology to employee's performance of BPJS Ketenagakerjaan Jawa Tengah and DIY.The population in this study were employees of the BPJS Ketenagakerjaan Jawa Tengah regional offices and branch offices Semarang 1 which consisted 64 people. The data were obtained by using the